2015
DOI: 10.1002/stem.2188
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Wnt-Regulatory Protein CTNNBIP1 by microRNA-214 Enhances the Stemness and Self-Renewal of Cancer Stem-Like Cells in Lung Adenocarcinomas

Abstract: A novel hypothesis in cancer biology proposes that cancer growth is driven by cancer stem-like cells (CSLCs), also called tumor-initiating cells, which can self-renew and differentiate into multilineage progeny in a fashion similar to stem cells. However, the impact and underlying mechanisms of this process in lung adenocarcinoma (LAC) remain to be elucidated. Here, we report that microRNA-214 (miR-214) contributes to cell self-renewal by directly targeting catenin beta interacting protein 1 (CTNNBIP1), a memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Then, he found BMp9 can inhibit the growth and migration of LUAD A549 cells through the MApK/ERK and NF-κB pathways. It was also reported that Wnt signaling pathways were related with LUAD (53)(54)(55).…”
Section: Discussionmentioning
confidence: 97%
“…Then, he found BMp9 can inhibit the growth and migration of LUAD A549 cells through the MApK/ERK and NF-κB pathways. It was also reported that Wnt signaling pathways were related with LUAD (53)(54)(55).…”
Section: Discussionmentioning
confidence: 97%
“…However, this is no way to fully define the function of one gene. For instance, a review of the literature reveals that TWIST1 overexpression in mammary epithelial and cancer cell lines has been shown to promote tumor stemness (25), and miR-214 enhances the stemness and self-renewal of cancer stem-like cells (CSLCs) in lung adenocarcinomas by targeting CTNNBIP1 (22). This indicates that TWIST1 may play a critical role in CSLCs self-renewal and stemness by upregulating miR-214 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, increasing evidence has shown that the CTNNBIP1/β-catenin interaction can prevent the formation of the β-catenin/TCF/ LEF complex. As a result, it prevents the activation of the Wnt/β-catenin signaling pathway [95][96][97][98]. The upregulated circRNA_102171 facilitates the malignant behavior of papillary thyroid cancer by regulating the CTNNBIP1-mediated activation of the Wnt/β-catenin pathway.…”
Section: Wnt Pathway-related Circrnasmentioning
confidence: 99%